O ensino da didática nos cursos de licenciatura em Pedagogia das universidades públicas do Ceará: concepções e possibilidades - Sátiro, Charmênia Freitas de (2013)
Recent studies nationwide in the area of teacher training point to the fragility of the Curriculum as a field of knowledge of pedagogy, considered in designing technical and instrumental. In this context, our research aims to integrate such studies to understand the context of this discipline in Ceará. We aim to understand the general characteristics Didactic discipline has assumed in the course of Pedagogy of public universities in the state, knowing the teachers and the design of which is registered in their teaching plans. We ask: What teachers teach didactics? What proposals and content of their teaching plans? What is the methodological approach applied by these professionals? Characteristics that this discipline has taken? What are the challenges you face? What is the Curriculum on pedagogical? To answer these questions we conducted a qualitative study in the UFC (Federal University of Ceará), UECE (State University of Ceará), URCA (University Cariri Regional) and UVA (University Vale do Acaraú). We use as instruments of data collection semistructured interviews with teachers Didactic Pedagogy course these institutions, programs and documentary analysis of the discipline, as well as a bibliographic research didactics. The research revealed that the discipline teaching in public universities of Ceará is crafted in a multidimensional way, in a dialectical relationship between society, education, Education and the School of Basic Education. Also revealed the possibilities of pedagogical innovation present in research practices and action-reflection Teachers Teaching.